2003
DOI: 10.1289/ehp.6433
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activation of cord blood mononuclear cells and cytokine production in a remote coastal population exposed to organochlorines and methyl mercury.

Abstract: Remote coastal populations that rely on seafood for subsistence often receive unusually high doses of organochlorines and methyl mercury. Immunosuppression resulting from prenatal exposure to organochlorines has been reported in wildlife species and humans. In this study, we assessed lymphocyte activation and associated cytokine secretion in 47 newborns from a remote maritime population living on the Mid and Lower North Shore regions of the St. Lawrence River (Québec, Canada; subsistence fishing group) and 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…For these studies, TNFα was selected as the representative pro-inflammatory, and IL-10 as the anti-inflammatory, cytokine for analysis in that each were previously monitored by Bilrha et al (2003) to investigate their association with prenatal exposure to some OC. Several other studies have monitored the impact of different pesticides on levels of these cytokines as well (see Duramad et al, 2007), but our study is the first performed on Egyptian infants.…”
Section: Laboratory Investigations Of the Infantsmentioning
confidence: 99%
See 2 more Smart Citations
“…For these studies, TNFα was selected as the representative pro-inflammatory, and IL-10 as the anti-inflammatory, cytokine for analysis in that each were previously monitored by Bilrha et al (2003) to investigate their association with prenatal exposure to some OC. Several other studies have monitored the impact of different pesticides on levels of these cytokines as well (see Duramad et al, 2007), but our study is the first performed on Egyptian infants.…”
Section: Laboratory Investigations Of the Infantsmentioning
confidence: 99%
“…Furthermore, O'Neill (2002) suggested that binding of dioxin-like compounds to the aryl hydrocarbon receptor (a transcription factor) can antagonize the effects of another transcription factor, nuclear factor (NF)-κB, an important regulator of immune and inflammatory gene expression (Sonne et al, 2006). Bilrha et al (2003) found that newborns exposed to OC in utero had significantly decreased TNFα production, suggesting that these children may be more susceptible to infection. These data indicate further that early exposures to environmental toxicants can directly impact the development and function of a child's immunity.…”
Section: Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…Organochlorine pesticides are carcinogenic in animals (International Agency for Research on Cancer, 1987) and the immunotoxicity of selected organochlorine pesticides has been documented in vitro (Bilrha et al, 2003), in ovo (Lavoie and Grasman, 2007), as well as in animals (Bernhoft et al, 2000) and in human fetal, neonatal and infant immune systems (Repetto and Baliga, 1997;Dewailly et al, 2000;Heilmann et al, 2006). Concern about organochlorine pesticides as risk factors for cancer has prompted research into determinants of blood levels and adipose tissue concentrations of these compounds in the general population and a growing number of epidemiological studies have investigated blood or adipose levels of organochlorine pesticides and their metabolites in association with cancer, neurodevelopmental effects, immunotoxicity and reproductive outcomes (Longnecker et al, 1997;WHO, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of organochlorines were significantly higher in the subsistence fishing group. In vitro secretion of tumour necrosis factor-alpha correlated inversely with organochlorine concentration [34].…”
Section: Discussionmentioning
confidence: 93%